A study on the effects of piled-raft foundations on the seismic response of a high rise building resting on clayey soil. Issue 145 (June 2021) - Bolouri Bazaz, HamidReza; Akhtarpour, Ali; Karamodin, Abbas
Abstract: Piled-raft foundations are often used to transfer the structural load to the depth of the soil and tall structures can be constructed on medium to soft soils by utilizing a group of piles. The static effects of a group of piles are quite evident while their dynamic effects are quite unknown and therefore, not considered in the design of the superstructure. In the present research, the performance of pile-raft foundations on the seismic response of a 20-story benchmark building resting on soft clayey soil has been investigated using a 2D finite difference model, namely FLAC. The study has been carried out by analyzing the seismic response of the structure with and without pile-raft foundations, on the surface and inside an excavation. The results show that when the structure is constructed on the surface, piled-raft foundations have a significant beneficial effect on the seismic response of the superstructure, for instance a 40% decrease in the base shear. In the case where the structure is located inside an excavation the use of piled-raft foundations are not noteworthy and do not have a considerable effect. The results of this study give an insight on the effects of pile-raft foundations on the seismic response of a superstructure to overcome the current shortage of information in this area and to better predict the behavior of tall structures in soft soil situations. Highlights: Seismic effects of pile-raft foundations are not considered in the design of high-rise buildings. A piled-raft foundation can significantly reduce the seismic response of a superstructure. Excavation can disable the beneficial effects of piled-raft foundation on the superstructure's response. Excavation may not be beneficial for high-rise buildings resting on soft and clayey soils. Soil-structure interaction (SSI) studies can economically improve the design of tall structures on soft soils.